2022
DOI: 10.3389/fnins.2022.882322
|View full text |Cite
|
Sign up to set email alerts
|

Clinical vitamin D levels are associated with insular volume and inferior temporal gyrus white matter surface area in community-dwelling individuals with knee pain

Abstract: ContextVitamin D is an essential, fat soluble micronutrient long-known for its effects on calcium homeostasis and bone health. With advances in technology, it is being discovered that Vitamin D exerts its effects beyond the musculoskeletal system. Vitamin D has since been noted in nervous system health and functioning, and is becoming a target of interest in brain health, aging, and chronic pain outcomes.ObjectivesWe and others have previously shown that deficient Vitamin D status is associated with greater pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…Neuroimaging studies have consistently shown insular activation across various noxious modalities and body parts, indicating its role as a central hub for processing pain stimuli regardless of the source [ 52 ]. Functional magnetic resonance imaging offers a non-invasive means of measuring neuronal activity in the human brain by detecting changes in activity and generating signals.…”
Section: Reviewmentioning
confidence: 99%
“…Neuroimaging studies have consistently shown insular activation across various noxious modalities and body parts, indicating its role as a central hub for processing pain stimuli regardless of the source [ 52 ]. Functional magnetic resonance imaging offers a non-invasive means of measuring neuronal activity in the human brain by detecting changes in activity and generating signals.…”
Section: Reviewmentioning
confidence: 99%
“…Many environmental factors may influence pain and/or sensorimotor behavior. And as in animal models, environmental factors range widely in humans, and include the chemical composition and physical features of the diet, drugs of abuse, toxins, level of physical activity, training and fitness, past pain history, social stressors, sociocultural factors, adverse life circumstances, sleep disruption, and gender roles and expectations, to injury, inflammation, diseases, muscle atrophy, and other alterations of peripheral tissues which can lead to pain ( Sanford et al, 2002 , Wise et al, 2002 , Davidson and McEwen, 2012 , Finan et al, 2013 , Fillingim, 2017 , Bjørklund et al, 2019 , Polli et al, 2019 , Lesnak and Sluka, 2020 , Sessle, 2021 , Strath et al, 2022 , Lesnak et al, 2023 ). While many of these factors have not been specifically studied in relation to pain-related sensorimotor behaviors in humans, some of these factors have been shown to contribute to the sex and inter-individual differences in pain sensitivity and sensorimotor behaviors noted above ( Mogil, 2012b , Mogil, 2020 , Sawicki et al, 2021 ).…”
Section: Pain and Sensorimotor Interactionsmentioning
confidence: 99%
“…• La PTH actúa sobre el túbulo proximal, la porción ascendente del asa de Henle y el túbulo contorneado distal, promoviendo la reabsorción rápida de calcio. La reabsorción de calcio en el riñón se modula mediante PTH, 1,25(OH)2D3 y estrógenos; reduciendo la expresión de los niveles de TRPV5, calbindina D28k, PMCA1b y NCX1 en las células renales (4,5).…”
Section: Los Efectos Del Calcio En El Hueso Y El Papel De La Parathor...unclassified
“…El calcio sérico está ligado a proteínas (principalmente albumina) en un 40%, a aniones como citrato, sulfato o fosfato en un 9% o en un estado ionizado 33%. Siendo el calcio ionizado (biológicamente activo) la forma viable para la activación de procesos fisiológicos esenciales, sus valores normales son 4,6 -5,0 mg/dl y 1,15 a 1,25 mmol/L (1)(2)(3)(4) . El calcio además de contribuir en la rigidez y densidad ósea también ejerce acciones sobre la función neuromuscular, la cascada de coagulación, la permeabilidad celular, la activación enzimática, el funcionamiento hormonal y la muerte celular programada (5,6).…”
Section: Introductionunclassified